PO.4.92 Taxonomy, treatment, targets and remission in systemic lupus erythematosus: the 3TR-SLE study protocol. (27th September 2022) - Parodis, I; Voskuyl, AE; Alarcón-Riquelme, ME; Beretta, L
Abstract : Purpose: Taxonomy, Treatment, Targets and Remission (3TR) is a transdisciplinary consortium funded by the Innovative Medicine Initiative (IMI) and European Federation of Pharmaceutical Industries and Associations (EFPIA), aimed at performing a longitudinal multi-dimensional molecular analysis in patients with autoimmune, allergic, and inflammatory diseases. The main hypothesis of the 3TR project is that data obtained from multilevel omics analysis across seven different diseases will identify shared biological pathways that better predict response or non-response to therapies despite their differences in terms of clinical phenotypes and pathogenetic mechanisms. Systemic lupus erythematosus (SLE), rheumatoid arthritis, multiple sclerosis, inflammatory bowel disease, asthma, and chronic obstructive pulmonary disease are the chronic disorders that will be investigated for shared biomolecular pathways. Methods: Centralised and standardised clinical data and sample collections will be a resource for studies and knowledge. Patients from multiple European centers are recruited for a longitudinal clinical follow-up and collections of blood, urine, stools, saliva, and relevant tissue samples at multiple timepoints. Among other analyses, we plan to perform transcriptome profiling in blood and tissues, including single-cell analyses, as well as analysis of the metabolome, microbiome, and lipid mediators in urine and stools. Data will be available and integrated through highly innovative bioinformatics analysis platforms. Results: For SLE, two observational prospective studies have been designed: (i) the flare biomarker study (3TR-SLE 1), and (ii) the response biomarker study (3TR-SLE 2). In 3TR-SLE 1, patients with quiescent SLE (no BILAG A or B) are recruited from 25 European tertiary referral centres and are followed up until they develop a flare, or for a maximum of 24 months. Clinical assessments and sampling are conducted at baseline and at flare, or at 24 months if no flare occurs. Patients who develop a flare (BILAG A or B resulting in a change in therapy) are asked to participate in 3TR-SLE 2, where assessments and sampling occur on 5 occasions through 52 weeks (baseline and week 6, 12, 26, 52). Patients at flare during screening are directly recruited in 3TR-SLE 2. Patients who develop flares during follow-up after an initial response are assessed and sampled at 2 additional timepoints (26 and 52 weeks post-flare). The 3TR-SLE study flowchart and inclusion and exclusion criteria are detailed in the figures . We intend to include 1000 patients with SLE in 3TR-SLE 1, and 330 in 3TR-SLE 2. Conclusions: Several innovations are expected within the 3TR project towards increased knowledge of pathogenetic mechanisms underlying clinical SLE phenotypes, and towards unraveling the complexity of the SLE biomolecular heterogeneity, the pathways of response or non-response to treatment, and the processes leading up to disease flare. Insights from studies within SLE and across 3TR diseases will facilitate evidence-based counselling and prevention, drug repurposing, personalised decision-making, and improved long-term prognosis for people living with SLE.